Coastal karst aquifers and submarine springs: what future for their water resources? - Fleury, Perrine; Pistre, Séverin; Bakalowicz, Michel (Comptes Rendus. Géoscience, 2022)
This paper is intended to be a reminder of a series of scientific works whose origin is largely attributable to G. de Marsily, without attempting to make an exhaustive overview of submarine springs and coastal karst aquifers. The main results show that coastal karst aquifers with their submarine outlets and the possibility of natural seawater intrusion are particularly fragile and must be studied and managed with appropriate tools. For the coming decades, the evolution of the climate as results from the IPCC scenarios leads us to question the effects of the increase of sea level on this coastal resource, and the effects of frequent and severe droughts, added to an increase in withdrawals from aquifers caused by the coastalisation of the population.